2008
DOI: 10.1038/ajh.2008.175
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Aldosterone-to-active-renin Ratio: A Useful Tool for Predicting Resolution of Hypertension After Adrenalectomy in Patients With Aldosterone-producing Adenomas

Abstract: Although all the subjects showed lowering of BP after surgery, and the age-BP relationship was restored, the long-term cure rate of APA subjects was 40%. The UAAR ratio, by comparison with other classical hormonal features of primary aldosteronism, was the best independent predictor of the cure of hypertension after adrenalectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 37 publications
0
16
1
Order By: Relevance
“…This is in line with previous observations that also showed that the A UR /R ratio is also of good predictive value whether or not hypertension is reversible after adrenalectomy for APA. 19,20 As a limitation, most of the PA patients were under antihypertensive therapy at the time of screening and the present retrospective study did not assess the influence of various antihypertensive drugs on the laboratory parameters. In addition, sodium intake also influences the ARR and the current study did not analyze the effect of low sodium intake versus high sodium intake on the aldosterone excess parameters in the same patients.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This is in line with previous observations that also showed that the A UR /R ratio is also of good predictive value whether or not hypertension is reversible after adrenalectomy for APA. 19,20 As a limitation, most of the PA patients were under antihypertensive therapy at the time of screening and the present retrospective study did not assess the influence of various antihypertensive drugs on the laboratory parameters. In addition, sodium intake also influences the ARR and the current study did not analyze the effect of low sodium intake versus high sodium intake on the aldosterone excess parameters in the same patients.…”
Section: Discussionmentioning
confidence: 90%
“…The urinary unconjugated (free) aldosterone-to-active renin ratio (A UR /R) proved to be a good independent predictor for surgical curability after adrenalectomy, in subjects with aldosteroneproducing adenomas (APAs). 19,20 Recently, our group has shown the usefulness of the serum sodium to urinary sodium to (serum potassium) 2 to urinary potassium (SUSPPUP) ratio in the diagnosis of PA. When calculated from synchronous measurements of sodium and potassium in serum as well as in urine in a fasting state, the SUSPPUP ratio reflects the mineralocorticoid excess and was proposed as a cheap and rapid tool in the screening for PA. 21 The present study was performed to assess the usefulness of different parameters in the first line screening for PA, including correction for plasma renin concentration or/and urinary sodium excretion.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 Based on age, diabetes mellitus, and angina pectoris, which remained significant in a multivariate model, we calculated a sum score associated with an adverse outcome. As shown in Figure 2, patients with a score of Ն2 had an increased risk for death.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have presented results showing that older age, larger tumor size, higher urinary aldosterone-renin ratio, higher BMI, and family history of hypertension are factors affecting the complete hypertension cure after adrenalectomy [9,10,11,16]. In particular, a recent study that used ARS to determine the score found female gender, use of ≤2 antihypertensive agents, BMI <25, and duration of hypertension <6 years to be good predictors [10].…”
Section: Discussionmentioning
confidence: 99%
“…More interestingly, Zarnegar et al [10] recently developed the Aldosteronoma Resolution Score (ARS), which is a simple scoring system to help clinicians predict the likelihood of complete hypertension cure after adrenalectomy. However, several studies found no association with complete hypertension cure for each of the supposed factors [11,12,13,14,15,16]. Furthermore, Steichen et al [4] pointed out that the ARS models, the only prediction model validated to date, provide only a weak prediction of hypertension cure in individual patients.…”
Section: Introductionmentioning
confidence: 99%